To Use or Not to Use ... The Intellectual Historian and the Isms : A Survey and a Proposal - Cesare Cuttica (Etudes Epistémè)
This essay examines the role of ism-categories in history-writing. Very often unconsciously used, isms permeate not just scholarly work but also everyday parlance – and yet neither outside of nor within academia do people often ask exactly why and how we use them. What do they mean ? What types of things are they supposed to encapsulate ? Would it be possible to do without them or, rather, are they part and parcel of our language in its multiple applications in life and to different fields of intellectual investigation ? Without pretending to provide an exhaustive account of this complex matter, this article presents an overview of some of these issues through references to a chronologically and thematically varied spectrum of sources ; it unveils some significant early modern instances of isms and makes a small theoretical contribution to the field of intellectual history. Departing from a widespread epistemological approach for the study of history, this essay suggests that to use isms can be both useful and important in the attempt to understand the past, its languages, ideas, people and systems of beliefs. In fact, the following pages show how a less essentialist use of isms might provide new meaningful readings of past thoughts and events. Finally, it is here argued that to reflect on how isms are employed in historical research can serve to cast light on how history is written now. By rethinking the role of the intellectual historian in dealing with isms, some methodological reflections on the practice of history-writing as an act of observation as much as one of creation will also be advanced.